Variabilidade de componentes de produção de feijão e suas relações com caracteres da qualidade fisiológica das sementes - Olivo, Franciele (2009)
Genetic variability in beans have great importance in breeding programs to improve productivity traits and can be used to improve the seeds laboratory manipulation work. Regarding the seeds, the cultivated beans offer great variability, presenting a variety of grain shapes, size and color, however, greater knowledge of how these factors affect the current procedures adopted by the analysis of seed is required. Therefore, the aim of this essay was to quantify the genetic variability among different genotypes of beans from southern Brazil, cultivated and crioulos , for traits related to the physical and physiological quality of the seeds. The results of this study show variability among the genotypes studied, both for phenotypic traits as regarding those evaluated in the laboratory as indicative of seeds quality. The genetic distance in beans is in large part a result of the traits that discriminate the size and shape of seeds, as the thickness of the skin is highly correlated with traits that show the size and shape of bean seeds. Genotypes as Iraí, Chocolate Sobradinho, Vermelho Itajaí, Preto Comprido and Vermelho Escuro, by presenting great genetic variability in relation to others employed in the study are indicated in order of increasing genetic variability of beans. Traits considered as indicative of seeds strength such as CE, TG, CP and EA do not maintain association with traits that show size and shape of seeds.